Implementation of the Teaching on the Life of the Apostle Paul in Serving Based on 2 Timothy 3:10-17 - Soelistiyo , Daniel Zacheus; Suparti, Hana; Purwoko, Paulus Sentot; Lestari, Ana (International Journal of Culture and Religious Studies, 2021)
The pastor cannot be separated from his ministry life. In the church, the pastor is a leader, the attitudes and actions of pastors are often imitated by their congregation. Therefore, the pastor must maintain the attitudes and actions of his congregation as well as possible, the most important thing is that he must be able to set an example for others. For this reason, this article describes Paul's life teaching in serving as the goal in this writing which is beneficial for the implementation of the shepherd in serving God and others. Using descriptive qualitative method with literature study and analysis approach. So it can be concluded that the implementation of teaching about the life of the Apostle Paul in serving is based on 2 Timothy 3:10-17, among others: The Apostle Paul's Way of Life (Verse 10a). The Patience of the Apostle Paul (Verse 10b). The love of the Apostle Paul (Verse 10c). Perseverance of the Apostle Paul (Verse 10d). Live Hold on to the truth (Verse 14). Seek to know the Scriptures (Verse 15a). Wisdom (Verse 15b). Faith in Jesus (Verse 15). Living in the Word (Verse 16) Willing to Teach God's Word (Verse 16a). Willing to admit mistakes (Verse 16b). Willing to correct behavior (Verse 16c). Willing to be educated in the truth (Verse 16d). Willing to do good (Verse 17). All of this can be a guide for pastors in implementing Paul's teachings for the church and its ministry entrusted by God.